Simulation in Urological Training: The Hybrid Model of Institute of Kidney Diseases Peshawar A Comparative Study - Liaqat Ali, Muhammad Shah, Mohammad Shahzad, Faiza Hayat, Mohammad Hanif, Nasir Orakzai (Pakistan Journal of Medical & Health Sciences, 2023)
Background:"I fear the man who has practised one kick 10,000 times." Lee Bruce This aphorism highlights the growing importance of simulation in postgraduate urology training, especially during the COVID 19 pandemic, when all teaching and training activities were stopped, jeopardising postgraduate residents' education. Postgraduate residents must perform hours of surgical training to overcome urological learning curves. According to study, residents educated on simulators boost their summative scores. By introducing simulation to urology training in a way comparable to the well-known Halsted apprenticeship model, the current study emphasises the hybrid model of IKD. Objective: to compare the formative assessment results between residents taught on simulators and residents in the conventional apprenticeship model on factors of communication skills, technical competence, and overall capacity to conduct procedure on OSAT and DOPS. Material & Methods: from 2019 to 2021 this comparative study was conducted in the Department of Urology by Team C at the Institute of Kidney Diseases Peshawar. Group A (10 residents) and Group B (10 residents, 5 from the second and third years) received STEPS method OT instruction in the first phase. These simulators were used to impart knowledge to Group "B" Harvey for counseling and medical examinations Simulator for PCNL The second phase included a six-month training assignment swap between the two groups. A standard QSAT and DOPS proforma was used to evaluate each resident. Data analysis was done using SPSS 24.0. Results: Residents in Group A, who were originally exposed to the conventional technique, considerably outperformed Group B on Harvey (mean: 50.5; standard deviation: 2.21.1) in terms of communication skills, professionalism, and ethical concern during the first phase (p 0.001). However, the Group p0.05 shown considerably higher technical proficiency and overall process performance capacity. The mean technical skill and overall capacity to finish the process had a somewhat positive association in phase 1 in favour of group B (r=0.630, p 0.01). All QSAT and DOPS metrics significantly improved in the second phase. However, both groups did not vary significantly (p> 0.05). According to Pearson coefficient correlation, both groups considerably overcame their gaps in technical proficiency, communication skills, and procedural competence. (P= 0.001) Results are shown in Figures 1 through 06 and Tables 1 through 2. Conclusion: To improve the standard of urology residency in Pakistan, a hybrid paradigm that includes both simulation and actual performance is necessary. Keywords: simulation, education, learning, skills, innovation, urology